Lactobacillus plantarum-derived indole-3-lactic acid ameliorates colorectal tumorigenesis via epigenetic regulation of CD8+ T cell immunity - Zhang, Qingqing; Zhao, Qing; Li, Tao; Lu, Longya; Wang, Fei; Zhang, Hong; Liu, Zhi; Ma, Huihui; Zhu, Qihui; Wang, Jingjing; Zhang, Xuemei; Pei, Yang; et al. (Cell metabolism, 2023)
Previous studies have shown that Lactobacillus species play a role in ameliorating colorectal cancer (CRC) in a mouse model. However, the underlying mechanisms remain largely unknown. Here, we found that administration of a probiotic strain, Lactobacillus plantarum L168 and its metabolite, indole-3-lactic acid, ameliorated intestinal inflammation, tumor growth, and gut dysbiosis. Mechanistically, we indicated that indole-3-lactic acid accelerated IL12a production in dendritic cells by enhancing H3K27ac binding at the enhancer regions of IL12a that contributed to priming CD8+ T cell immunity against tumor growth. Furthermore, indole-3-lactic acid was found to transcriptionally inhibit Saa3 expression related to cholesterol metabolism of CD8+ T cells through changing chromatin accessibility and subsequent enhancing function of tumor-infiltrating CD8+ T cells. Together, our findings provide new insights into the epigenetic regulation of probiotics-mediated anti-tumor immunity and suggest the potential of L. plantarum L168 and indole-3-lactic acid to develop therapeutic strategies for patients with CRC. [Display omitted] •L. plantarum L168 and its derived ILA ameliorate colorectal tumorigenesis•ILA accelerates IL12a production in DCs to prime anti-tumor immunity of CD8+ T cells•ILA enhances function of CD8+ T cells through epigenetic mechanisms•ILA inhibits expression of Saa3 in CD8+ T cells to reduce tumor growth of CRC The underlying anti-tumor immune mechanisms for probiotics preventing colorectal cancer remain largely unknown. Zhang et al. report that a strain of probiotics, L. plantarum L168 and its derived metabolite, indole-3-lactic acid, ameliorate colorectal tumorigenesis through contributing to anti-tumor immunity of CD8+ T cell via epigenetic regulation.